Monitoring the lung during mechanical ventilation - Mat Nor, Mohd Basri (2011)
Techniques to monitor the respiratory system during mechanical ventilation have evolved significantly over the years. When integrated with the physical examination, these tools aid the management of respiratory disease, ultimately leading to safer and more effective care for all mechanically ventilated critically ill patients. Respiratory monitoring tools allow for titrating therapeutic interventions to the patient’s disease state, if used correctly can facilitate optimal respiratory support and aid in weaning to extubation. With close monitoring, aberrations or changes in physiologic states can be detected before disease progression, allowing for early interventions and prevention of worsening disease. Paramount to optimal management is not only selecting the correct mode and ventilator settings for the underlying disease (e.g. ARDS, COPD, Asthma, broncho-pleural fistula), but also monitoring physiologic changes that occur from the disease state, or in response to therapeutic interventions. Monitoring respiratory mechanics is essential to reduce complications related to mechanical ventilation and to monitor recovery from respiratory failure. In intensive care, common means of respiratory monitoring used are work of breathing measurements, and flow-volume and pressure-volume loops. The availability of ventilator graphics and waveform analysis has had a tremendous impact on the science of mechanical ventilation. Through the analysis of these pressure, volume an flow waveforms, intensive care physician can now more accurately assess not only the current state of lung function but the status of patient-ventilator interaction as well. Role of ventilator graphics include identifying pathophysiologic processes, recognizing a change in patient’s condition, optimizing ventilator settings and treatment, determining effectiveness of ventilator settings detect adverse effects of mechanical ventilation and minimize risk of ventilator-induced complications. F-V loops are particularly useful in diagnosing the type of respiratory disease present (restrictive vs. obstructive). In lower airway obstruction they have a characteristic shape which may change in response to bronchodilators and in large airways they can help identify the type of obstruction (fixed or variable) if obtained while spontaneously breathing or if the ETT lies above the level of obstruction. P-V loops are useful to help to determine optimal lung recruitment, compliance and overdistension